PROBLEMATIKA PEMBELAJARAN IPA: ANALISIS KESULITAN SISWA DALAM MEMAHAMI MATERI DAN SOLUSINYA - Susilasari Susilasari; Rian Vebrianto; Muh Habibi; Yovita Yovita (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2025)
Education in the era of globalization that demands learning that is all technology according to the 21st century, on the other hand, remote areas have difficulty reaching learning according to the demands of the times. However, students must still understand the learning material. The purpose of this study was to determine the material that is considered difficult in the subject of science for grade IV of elementary school. And how to find solutions to solve this problem in elementary school. The methodology of this study uses the Mixmethod research type, which is presented with quantitative data then clarified with qualitative data. In this study, involving 32 respondents of grade IV students from elementary school and 2 science teachers, This study used questionnaire instruments, interview sheets, and observation sheets. Data were collected by going directly to the field and analyzed using descriptive analysis for qualitative and interview analysis for qualitative so that the data obtained became comprehensive, The results of this study are known that 3 materials are considered difficult for material, Changes in the form of objects there are 13 students (40.62%) and energy there are 11 students (36.67%) and there are 8 students or (25%) have difficulty understanding the material force. It can be concluded that the solution for difficult material in science subjects, especially learning using audio-visual media, image media, and learning videos, is maximized by learning by implementing a contextual learning approach so that students can develop more efficient learning skills